Influence of rainfall, air temperature, physical and chemical water profiles on Cyanobacteria Biovolume in Slim River lake, Perak, Peninsular Malaysia - Yonis Ahmed Kitan (2022)
This study aimed to identify the influence of rainfall, air temperature, physical and chemical water profiles on cyanobacteria biovolume in Slim River Lake, Perak, Peninsular Malaysia. Water samples were collected twice per month for 12 months in five sampling stations (S1-S5) to represent the lakes overall condition. Samplings were consistently conducted at the same time in the morning to reduce the influence of surrounding air temperature variations. The physical, chemical, and biological parameters were analysed according to American Public Health Association (APHA) standard methods. Rainfall and air temperature data were obtained from the Malaysian Meteorological Department. Data were successfully collected and the results indicated that Slim River Lake's physical, chemical, and biological water profiles were highly variable on a temporal scale. Total phosphorus, total nitrogen, chemical oxygen demand, chlorophyll-a and biovolumes of Microcystis spp. were recorded as 0.20-1.96 mg/L, 1.0- 4.2 mg/L, 9.50-82.0 mg/L, 2.08-132.05 g/L, 6.13106- 1.65108 m3 /mL, respectively. These parameters were recorded at levels exceeding the recommended limit values by National Lake Water Quality Criteria and Standards (NLWQS). Temporal fluctuations in physical, chemical, and biological profiles cannot be generalized into similar patterns. Rainfall and air temperature ranged as 36.3-642.5mm and 30.71-35.0oC, respectively. Rainfall and air temperature explained up to 72.3% and 77.3% variation in lake water quality. Multivariate Principal Component Analysis (PCA) suggested that 71.5% of chlorophyll-a variation and 70.2% of Microcystis spp. biovolumes variation can be explained by changes in rainfall, air temperature, physical and chemical water parameters. In conclusion, this study successfully showed that the physical, chemical and biological profiles in the Slim River Lake are variable and influenced by the variability of local rainfall and air temperature. Moreover, parameters included in the PCA analysis can largely explain temporal changes of cyanobacteria biovolume. In implication, the study outputs are useful for lake quality assessment and rehabilitation strategy formulation to mitigate the impact of changes in physical, chemical and biological profiles.